Poverty as a barrier to antiretroviral therapy access for people living with HIV/AIDS in Kenya. Issue 2 (3rd April 2018) - Haacker, Markus; Birungi, Charles
Abstract : Understanding barriers to access to essential health services is critical for devising effective strategies to improve access and align such strategies with national health and development policy objectives. However, while considerable empirical evidence exists on correlates of HIV prevalence and populations at risk of contracting HIV, there is very little such evidence on access to antiretroviral therapy. This paper addresses this gap through a cross-sectional analysis of coverage of antiretroviral therapy and its correlates across 47 counties in Kenya. It considers health-sector and social factors, and applying instrumental variables to address error-in-variables and reverse-causality issues regarding HIV prevalence. Poverty was the most robust and — statistically and substantially — significant determinant of treatment coverage. The gap in treatment coverage between the poorest and richest counties amounted to about 40 percentage points and has not narrowed between 2012 and 2015. Health sector capacities independently played a role and exacerbated the poverty gap. For Kenya, the results suggest that policies on expanding treatment access need to be differentiated across counties to greatest effect and to align the HIV/AIDS response with national health and social policy objectives. Regarding global HIV/AIDS policies, the findings suggest a need to recognise "people left behind" owing to socio-economic and specifically poverty-related barriers to access to services.